Impact of COVID-19 on the communication of hospitals in Spain. Adaptations and evaluation by their professionals. - Costa-Sánchez , Carmen (2022)
COVID-19 has caused a transformation in the organizational structure of the healthcare system that directly affects the management of its communication. This article aims to know the communication strategy of hospitals in Spain in a context of normality and what have been the main changes and adaptation needs caused by the pandemic. For this purpose, the information is collected and analyzed from a structured questionnaire and two focus group with health communication professionals. The results obtained confirm that pandemic modifies the type of tasks carried out in the three communication areas and transforms both the information requested and the priority in the use of channels for its transmission. Furthermore the work concludes that the health crisis has accelerated the development of the digitization and of Spanish health and communication systems. Finally, the professionals consider that the pandemic has favored the knowledge and recognition of the communication function inside and outside the hospital.